2018
DOI: 10.1108/bpmj-01-2018-0021
|View full text |Cite
|
Sign up to set email alerts
|

Business process model patterns: state-of-the-art, research classification and taxonomy

Abstract: Purpose Patterns have proven to be useful for documenting general reusable solutions to a commonly occurring problem. In recent years, several different business process management (BPM)-related patterns have been published. Despite the large number of publications on this subject, there is no work that provides a comprehensive overview and categorization of the published business process model patterns. The purpose of this paper is to close this gap by providing a taxonomy of patterns as well as a classificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…The categories are generally chosen following the purpose of the study, and this choice is recognized as a crucial step in taxonomy development [10]. A deductive line of reasoning has been followed in this study to understand the domain of interest and propose the categories [15]. For each category, then, the dimensions of classification have been defined (Figure 2).…”
Section: Methodsmentioning
confidence: 99%
“…The categories are generally chosen following the purpose of the study, and this choice is recognized as a crucial step in taxonomy development [10]. A deductive line of reasoning has been followed in this study to understand the domain of interest and propose the categories [15]. For each category, then, the dimensions of classification have been defined (Figure 2).…”
Section: Methodsmentioning
confidence: 99%
“…They found that each paradigm affects the attributes assigned to BPM. Fellman et al analyzed 180 research articles for creating a taxonomy of business process patterns (2019). They concluded that there was no overarching pattern language for business process model patterns.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…They resemble Reijers and Liman Mansar's (2005) heuristics, but relate more closely to the actual control flow of business processes. Furthermore, Fellmann et al (2019) developed a taxonomy of business process model heuristics which provides an overview of the existing research in this field and helps identify relevant heuristics.…”
Section: Theoretical Backgroundmentioning
confidence: 99%